Research and test application of the new mud system KGAC-Plus at highly deviated wells with complex trajectory and geological conditions - Hoang Hong, Linh; Nguyen Thanh, Truong; Nguyen Xuan , Quang; Bui Van, Thom; Vu Van, Hung (Petrovietnam Journal, 2017)
Based on the successful research and application of the KGAC mud system, the authors from Vietsovpetro have continued researching and testing to improve the inhibition level of the KGAC mud system to form the KGAC-Plus mud system, especially in the construction of highly deviated wells with complex trajectory and geological conditions. Mud test results and the application results at 04 wells showed that the quality of KGAC-Plus has been clearly improved comparing with the KGAC mud system. The inhibition level of KGAC-Plus is equivalent to the ULTRADRIL mud system of MI SWACO, one of the best inhibitive water-based mud system nowadays.